PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DALAM MENCIPTAKAN PEMBELAJARAN YANG INTERAKTIF SELAMA KEGIATAN PLP DI SMA NEGERI 6 PALEMBANG - Desi Isnaniah; Imelda Gaury; Andrean Agriano; Samia Julyati Rizhas; Tri Mania; Hilallia; Muhamad Idris (PT. Hasba Edukasi Mandiri, 2026)
This article describes the application of Problem Based Learning (PBL) in creating interactive learning during the School Field Introduction Program (PLP) at SMA Negeri 6 Palembang. The article uses a descriptive qualitative approach because the focus is not to measure statistical effects, but to narrate classroom processes based on observation, field notes, and photo documentation. The PLP activities were carried out from March 2 to May 15, 2026, at SMA Negeri 6 Palembang, Jl. Sersan Sani Basuki Rahmat Palembang, under the supervision of Dr. Muhamad Idris, M.Pd. The findings show that PBL was implemented through contextual problems, group division, discussion, solution exploration, presentation, question and answer, reflection, and reinforcement by the teacher or PLP students. Classroom documentation shows the use of projectors, student presentations, group assistance, demonstrations, and guided reflection. The implementation of PBL made classroom interaction more visible because students were not only listening to explanations, but also discussing, asking questions, expressing ideas, and responding to their classmates. Although several obstacles appeared, such as uneven student confidence, limited discussion time, and the need for repeated guidance, the learning process could be managed through clear instructions, simple media, small group assistance, and closing reflection. PBL therefore became a relevant model for supporting interactive learning during PLP because it encouraged cooperation, communication, critical thinking, and problem-solving in a natural classroom setting.